Cytomegalovirus glycoprotein H genotype distribution and the relationship with hearing loss in children. Issue 8 (21st February 2014) - Paradowska, Edyta; Jabłońska, Agnieszka; Studzińska, Mirosława; Kasztelewicz, Beata; Zawilińska, Barbara; Wiśniewska‐Ligier, Małgorzata; Dzierżanowska‐Fangrat, Katarzyna; Woźniakowska‐Gęsicka, Teresa; Kosz‐Vnenchak, Magdalena; Leśnikowski, Zbigniew J.
<x xml:space="preserve">Abstract</x> Cytomegalovirus (CMV) is a leading cause of congenital infection and a leading infectious cause of hearing loss in children. The ORF UL75 gene encodes envelope glycoprotein H (gH), which is essential for CMV entry into host cells and the target of the immune response in humans. However, the distribution of gH variants and the relationship between the viral genotype, viral load, and sequelae in children infected with CMV is debated. The UL75 genetic variation of CMV isolates from 42 newborns infected congenitally with CMV and 93 infants with postnatal or unproven congenital CMV infection was analyzed. Genotyping was performed by analysis of PCR‐amplified fragments, and the viral load was measured by quantitative real‐time PCR. There were no differences in the distribution of gH genotypes in the children infected congenitally and postnatally. Mixed‐genotype infections with both gH1 and gH2 variants were detected in approximately 25% of the examined patients. No relationship between UL75 gene polymorphisms and the symptoms at birth was observed. The results suggest that the infection with gH2 genotype diminishes the risk of hearing loss in children (P = 0.010). In addition, sensorineural hearing loss was associated with CMV gH1 genotype infection in infants (P = 0.032) and a high viral load in urine (P = 0.005). In conclusion, it was found that the gH genotype does not predict clinical sequelae in newborn infants following congenital CMV infection. However, these results suggest that the gH genotype might be associated with hearing loss in children. J. Med. Virol. 86:1421–1427, 2014. © 2014 Wiley Periodicals, Inc.